“After getting the courage to go…” : an interpretative phenomenological analysis of the customer experience of people who stop going to therapy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Broadhurst, Sara (Massey University, 2023)
Objectives: The study investigated the customer experience of people who had chosen to stop going to therapy, after one to three sessions of 50-60 minutes. In addition, it sought to understand if this experience influenced their future likelihood of using therapy and what they would recommend to others about therapy. Design: Qualitative interview study. Methods: Six people participated in semi-structured interviews, of between 60 and 90 minutes, about their customer experience of therapy with a psychologist or counsellor in Aotearoa New Zealand, who stopped after one to three sessions. The qualitative experiential methodology of interpretive phenomenological analysis was applied to the interview transcripts. Results: Using the four customer experience stages as a framework, the analysis generated themes and subthemes which provided insight into the customer experience and dropout decisions. First, in the pre-experience stage negative connotations still exist about mental health, although these have improved over time. Second, in the pre-purchase stage, participants were anticipating the therapy experience, with subthemes of process and expectations. Third, in the purchase stage, the details matter. Included are four subthemes: the physical space, customer feelings, therapist in-session behaviours and the termination experience. Finally, in the post-purchase stage, participants remained optimistic about therapy, with the subtheme that participants would recommend therapy to others, but with caveats. The participants’ decision to engage in future therapy or to recommend therapy to others was not influenced by having an unsatisfactory experience. Conclusions: The results of research to date on the causes of client dropout from therapy is broadly inconclusive and there is little research from a qualitative or customer experience perspective. Considering each stage of the customer experience brings a different perspective to the variables that influence dropout. In addition, it provides valuable insight into the customer’s decision to terminate, the things that need to be true for people to participate in future therapy and what they say to others when recommending therapy. This study makes a number of contributions for therapists looking to reduce the dropout rate of people attending their service.
Keywords: 520302 Clinical psychology